The personality of freestyle snowboarders : implications for product development - Müller, Sabine (Array, 2008)
Summary: Several approaches with reference to customer involvement in the product development process can be found in the research literature. The majority of studies, focusing primarily on customer invol-vement in the product or service development process, are based on research in the area of new product development. However, these studies did not describe which customers or groups of custo-mers are suitable to be involved in the product development process of services. Meanwhile some researchers have drawn their focus on this topic. The empirical personality psychological traits approach as well as the differential psychology put the individual in the focus of the analyses. To this end, a research of snowboarders' personality profile and their involvement in product design was carried out on a sample of 50 respondents active in the alpine region of Austria, Switzerland and Italy. The results have revealed that snowboarders differ from general population. The stan-dard deviations of all five scales are lower for the freestyle snowboarders than for those of the reference population. Freestyle snowboarders are scoring higher on dimensions of extraversion, open ness to experience, compatibility and conscientiousness. This research is an attempt to bring together psychology and social leisure sciences and to derive new findings regarding this under-investigated extreme sport segment, which in many cases displays typical lead user consumers in the field of sport tourism